Experimental and computational VUV photoabsorption study of dimethyl carbonate: A green solvent. (September 2018) - Das, Asim Kumar; Krishnakumar, Sunanda; Rajasekhar, B.N.
Highlights: Electronic photoabsorption spectrum using synchrotron radiation of dimethyl carbonate (DMC) recorded in 7–11 eV region reported for the first time. Excited state energies and nature of the transitions using TDDFT methodology. Potential energy curves of the first few excited states studied to predict the photo-dissociation pathways. Analysis of photoabsorption spectra of DMC in VUV region substantiated with quantum chemical calculations. Abstract: VUV photoabsorption spectrum of dimethyl carbonate in the energy region 7–11 eV and its complete spectral analysis with the aid of quantum chemical calculations is reported for the first time. The spectrum recorded using synchrotron radiation comprises of weak bands overlapping a broad intense continuum. With a view to interpret possible vibronic structure, gas phase infrared spectrum in the region 500–4000 cm −1 is revisited. Density functional theory (DFT) and time dependent DFT (TDDFT) methodologies are used to obtain ground state geometry, vibrational frequencies and vertical excitation energies of dimethyl carbonate. The intense broad features in the spectrum could be attributed to valence transitions. Based on quantum defect calculations, energy ordering and symmetry, weak bands are designated as ns, np and nd type Rydberg transitions converging to the first five ionization potentials. The highest occupied molecular orbital is nonbonding in nature and largely localized on the oxygen atom of carbonyl group and quantum defect values obtained are consistent with excitation from oxygen lone pair. Excellent correlation is obtained between theoretically predicted (CAM-B3LYP levels of theory) and experimentally observed excited state energies. Potential energy curves of ground and first few excited states generated with a view to provide additional insights into their nature and further describe the observed spectra. The present study provides a comprehensive experimental and computation analysis of the VUV photoabsorption spectroscopy of dimethyl carbonate.